Impact of an Electronic Decision-Support System on Nursing Triage Process: A Usability and Workflow Analysis. Issue 2 (June 2021) - Agnihotri, Tanya; Fan, Mark; McLeod, Shelley; Borgundvaag, Bjug; Ovens, Howard; McCarron, Joy; Trbovich, Patricia
Purpose: To qualitatively contrast emergency department triage workflow using a paper-based triage system and an electronic decision-support tool (electronic Canadian Triage and Acuity Scale (eCTAS)). Methods: Triage nurses from a single institution were invited to perform triage assessments of mock patients using a paper-based triage system and eCTAS. These assessments were completed using simulation scenarios, some of which involved facilitators probing triage nurses' thoughts on the design of the eCTAS system. Participants were asked to "think aloud, " describing their thought patterns as they completed the triage process. Similar patient scenarios with the same Canadian Emergency Department Information System (CEDIS) presenting complaint and triage score were used for comparison between paper-based triage and electronic decision-support tool (eCTAS) conditions. Results: Eight participants completed at least two simulation scenarios for each condition and at least one usability scenario with eCTAS. The simulated encounters showed eCTAS provided several advantages to paper-based triage assessment process by shortlisting possible CEDIS complaints and preselecting relevant modifiers. However, usability concerns were identified with eCTAS including challenges related to data entry and eCTAS score overrides. Conclusions: Our study highlights several positive features of eCTAS and usability issues that should be addressed to enhance the intended use of eCTAS and support user adoption.